2005
DOI: 10.1136/hrt.2003.030601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of systemic hypertension on the assessment of aortic stenosis

Abstract: Objective: To determine the effect of systemic arterial hypertension on the indices of aortic stenosis (AS) severity. Methods: A severe supravalvar AS was created in 24 pigs. The maximum and mean pressure gradients across the stenosis were measured by Doppler echocardiography and by catheterisation. Both echocardiography and catheter data were used to calculate stenosis effective orifice area, energy loss coefficient, and peak systolic left ventricular wall stress. Measurements were taken both at normal aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 28 publications
8
93
0
4
Order By: Relevance
“…rAC is a major contributor to the development of systolic hypertension, contributing to LV afterload and decreased coronary flow during diastole, and it has been shown to be a strong predictor of LV dysfunction and adverse events 30, 31, 32, 33, 34. Patients with AS already have increased LV afterload because of valvular stenosis, and it has been demonstrated that rAC has a significant additive effect and contributes to LV dysfunction and occurrence of adverse outcomes 22, 35. In the present study, we showed that rAC induces a marked reduction in MG and V peak for any AS severity, even if flow is stable and even in the absence of hypertension.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…rAC is a major contributor to the development of systolic hypertension, contributing to LV afterload and decreased coronary flow during diastole, and it has been shown to be a strong predictor of LV dysfunction and adverse events 30, 31, 32, 33, 34. Patients with AS already have increased LV afterload because of valvular stenosis, and it has been demonstrated that rAC has a significant additive effect and contributes to LV dysfunction and occurrence of adverse outcomes 22, 35. In the present study, we showed that rAC induces a marked reduction in MG and V peak for any AS severity, even if flow is stable and even in the absence of hypertension.…”
Section: Discussionsupporting
confidence: 64%
“…The decrease in flow induced by hypertension leads to a reduction in transvalvular gradient and velocity. Kadem et al previously demonstrated in an animal model of supravalvular AS that acute hypertension induces a significant reduction in the peak and mean gradients as measured by catheter without significant decrease in mean transvalvular flow rate 22. In our animal study, the induction of hypertension resulted in a slight decrease in stroke volume but did not influence significantly the mean transvalvular flow rate.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Finally, it is worth emphasizing that the severity of aortic stenosis may be masked by the coexistence of hypertension (underestimated valve gradient); thus, the degree of AoS should be interpreted with caution when blood pressure is high and should be reassessed after the normalization of pressure 21 . Thus, despite the classic contraindication for patients with severe AoS, antihypertensive drugs should be considered when treating these patients when hypertension is associated with AoS.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension can be present in 68% of patients with severe aortic stenosis [51]. In severe supravalvar aortic stenosis model, systemic arterial hypertension may result in significant impairement of the aortic compliance [52]. A study based on 3.39 million discharges in Ireland revealed that the prevalence of hypertension was 21.0% in the patients with aortic stenosis, and was 1.1% in those with aortic stenosis.…”
Section: Valvular Diseasementioning
confidence: 99%